Expression of SUMO enzymes is fiber type dependent in skeletal muscles and is dysregulated in muscle disuse - Namuduri, Arvind Venkat; Heras, Gabriel; Lauschke, Volker Martin; Vitadello, Maurizio; Traini, Leonardo; Cacciani, Nicola; Gorza, Luisa; Gastaldello, Stefano (The FASEB journal, 2020)
SUMOylation is a dynamic, reversible, enzymatic drug‐targetable post‐translational modification (PTM) reaction where the Small Ubiquitin‐like Modifier (SUMO) moieties are attached to proteins.